Evaluating the Moisture Susceptibility of Asphalt Mixtures Containing Aluminum Dross as a Filler (Journal of Engineering, 2024)
One of the most essential components of asphalt pavements is the filler. It serves two purposes. First, this fine-grained material (diameter less than 0.075 mm) improves the cohesiveness of aggregate with bitumen. Second, produce a dense mixture by filling the voids between the particles. Aluminum dross (AD), which is a by-product of aluminum re-melting, is formed all over the world. This material causes damage to humans and the environment; stockpiling AD in landfills is not the best solution. This research studies the possibility of replacing part of the conventional filler with aluminum dross. Three percent of dross was used, 10, 20, and 30% by filler weight. The MarshallMix design method was adopted to obtain the optimum asphalt content for the selected aggregate gradation. After that, the mixture was used to evaluate the moisture damage for controlandimproved mixtures. The compressive strength and tensile strength tests were used to estimate the moisture damage to the asphalt mixtures. It was observed that replacing a part of the limestone dust filler with aluminum dross would improve moisture damage resistance. This was approved since the maximum increase in tensile strength ratio (TSR)was found to be 13.42% at 20% of AD, and the maximum increase in the index of retained strength (IRS)was found to be 8.73% at the same AD percent.